Utilizing Evaporative Cooling for Efficient Thermal Management of Lithium-Ion Batteries in Electric Vehicles - Kashif Mushtaq (328962); 9 (Islamabad : USPCAS-E, NUST, 2024)
TH-572
Keywords: MS TEE Thesis; MS Thesis